2008
DOI: 10.1098/rspb.2007.1707
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone modulates aggression in sex-role reversed female African black coucals

Abstract: Testosterone is assumed to be the key hormone related to resource-defence aggression. While this role has been confirmed mostly in the context of reproduction in male vertebrates, the effect of testosterone on the expression of resource-defence aggression in female vertebrates is not so well established. Furthermore, laboratory work suggests that progesterone inhibits aggressive behaviour in females. In this study, we investigated the hormonal changes underlying territorial aggression in free-living female Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 60 publications
8
74
0
Order By: Relevance
“…Davis & Marler, 2003;Fraile, McEwen, & Pfaff, 1988;Kolhert & Meisel, 2001;de Sousa et al, 2010). Similar results were reported for a sex-role-reversed bird species, the African black coucal (Goymann et al, 2008). In a study by Goymann et al (2008), P4 concentrations of female coucals were reported to be significantly lower in individuals engaged in aggressive behaviour than in females assessed in nonaggressive contexts.…”
Section: Other Potential Hormonessupporting
confidence: 79%
See 1 more Smart Citation
“…Davis & Marler, 2003;Fraile, McEwen, & Pfaff, 1988;Kolhert & Meisel, 2001;de Sousa et al, 2010). Similar results were reported for a sex-role-reversed bird species, the African black coucal (Goymann et al, 2008). In a study by Goymann et al (2008), P4 concentrations of female coucals were reported to be significantly lower in individuals engaged in aggressive behaviour than in females assessed in nonaggressive contexts.…”
Section: Other Potential Hormonessupporting
confidence: 79%
“…Several studies have attempted to determine whether elevations of T accompany displays of female aggression as proposed by the 'challenge hypothesis' (Wingfield, Hegner, Dufty, & Ball, 1990), yet results are mixed from studies attempting to quantify such a relationship. For example, elevated levels of T were not present following aggressive behaviour in female European stonechats, Saxicola torquata (Canoine & Gwinner, 2005;Gwinner, R€ odl, & Schwabl, 1994), song sparrows, Melospiza melodia (Elekonich & Wingfield, 2000), spotted antbirds, Hylophylax n. naevioides (Hau, Stoddard, & Soma, 2004), dark-eyed juncos, Junco hyemalis (Jawor, Young, & Ketterson, 2006), and African black coucals, Centropus grillii (Goymann, Wittenzellner, Schwabl, & Makomba, 2008), but T concentrations were higher in buffbreasted wrens, Thryothorus leucotis (Gill et al, 2007), following exposure to a female decoy, and in dunnocks, Prunella modularis (Langmore, Cockrem, & Candy, 2002), after experimental removal of males encouraged competition among females.…”
mentioning
confidence: 97%
“…Females are generally larger than males and display male-typical behaviors such as territory defense and singing [32,39,42,85,86]. Females of such species are therefore conspicuous and good models for studying the neuroendocrine mechanisms underlying some behaviors such as resourcedefense aggression and, more generally, behavioral sex differences [32,45,118]. But even in species with conventional sex roles, where territorial males are much more conspicuous than females, simply increasing observation or catching effort, or diversifying the techniques used, are affordable and efficient solutions [e.g.…”
Section: Reducing the Sex-bias In Physiological Studiesmentioning
confidence: 99%
“…This effort now seems to have faded away for no apparent reason. The females from these studies were however caught in the same way as males, generally using mist-nets, sometimes combined with simulated territorial intrusion, and baited traps [see also 34,45,59,89,97,134].…”
Section: Reducing the Sex-bias In Physiological Studiesmentioning
confidence: 99%
“…Endogenous testosterone (T) in female birds has been shown in some studies to respond to social situations (Gill et al 2007) but not in others (Elekonich 2000;Jawor et al 2006;Navara et al 2006;Goymann et al 2008). The field evidence of an association between female natural T levels and social behaviour remains inconclusive at present (Cain and Ketterson 2012;Elekonich and Wingfield 2000;Goymann and Wingfield 2014).…”
Section: Introductionmentioning
confidence: 98%